A Study on Free Open Source Data mining Tools (International Journal of Engineering and Computer Science, 2014)
Today in this real world, where we deal with vast amounts of data, we are in a situation to extract the best among them. Data mining is a new and imminent trend to discover the information and knowledge from the existing data. The gained knowledge can be used for applications ranging from market analysis, fraud detection, and customer retention, to production control and science exploration. It uses machine learning, statistical and visualization techniques to discover the present knowledge in the form which is easily understandable by the users. The data mining tools are used to predict the future trends and behaviours of various business organisations and aid them to make good decisions for their growth and development. They search the databases for hidden patterns, and to make predictions beyond the mind-set of the experts. This paper explains about various open source data mining tools through which efficient predictive analysis can be done.